2017
DOI: 10.21767/2171-6625.1000205
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Extrapyramidal Syndrome in a Patient with Splenic Vein Thrombosis without Overt Hepatic Dysfunction

Abstract: Acquired hepatocerebral degeneration (AHD) is an extrapyramidal syndrome that develops secondary to hepatic dysfunction. It may accompany advanced liver disease and is related to the presence of portosystemic shunts. We describe a 44-year-old woman who presented with bleeding from gastric fundus varices secondary to splenic vein thrombosis and concomitant development of rapidly progressive extrapyramidal symptoms. No overt liver dysfunction was identified. Brain imaging demonstrated damage to the basal ganglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Sosso et al [1], found that there is an interplay between the primary visual cortex and short-term plasticity. Goldstein et al [2], presented a case of an extrapyramidal syndrome in the background of splenic vein thrombosis in a 44-year-old woman. Oh et al [3], evaluated the trends in the age of stroke in rapidly developing urban areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sosso et al [1], found that there is an interplay between the primary visual cortex and short-term plasticity. Goldstein et al [2], presented a case of an extrapyramidal syndrome in the background of splenic vein thrombosis in a 44-year-old woman. Oh et al [3], evaluated the trends in the age of stroke in rapidly developing urban areas.…”
mentioning
confidence: 99%
“…AHD may accompany advanced liver disease. Goldstein et al [2], described the case of a 44-year-old woman who in addition to suffering from splenic vein thrombosis, was bleeding from the gastric fundus varices and exhibited rapidly progressive extrapyramidal symptoms. Though, severe liver dysfunction was not identified, brain imaging revealed damage to the basal ganglia.…”
mentioning
confidence: 99%